인공지능을 이용한 학습부진 특성 추출 및 예측 모델 연구 - 양자영(Ja-Young Yang); 문경희(Kyong-Hi Moon); 박성호(Seong-Ho Park) (한국정보통신학회논문지, 2022)
The diagnostic evaluation conducted at the national level is very important to detect underachievers in school early. This study used an artificial intelligence method to find the characteristics of underachievers that affect learning development for middle school students. In this study an artificial intelligence model was constructed and analyzed to determine whether the Busan Education Longitudinal Data in 2020 by entering data from the first year of middle school in 2019. A predictive model was developed to predict basic middle school Korean, English, and mathematics education with machine learning algorithms, and it was confirmed that the accuracy was 78%, 82%, and 83%, respectively, in the prediction for the next school year. In addition, by drawing an achievement prediction decision tree for each middle school subject we are analyzing the process of prediction. Finally, we examined what characteristics affect achievement prediction. 국가수준에서 시행되는 진단평가는 학교에서 학습부진이 있는 학생을 조기 발견하는 것이 매우 중요하다. 본연구는 부산교육종단의 2019년 중학교 1학년의 데이터를 입력하여 2020년 성취여부를 판별하는 인공지능 모델을 구축하고 분석하였다. 머신러닝 알고리즘으로 중학교 국어, 영어, 수학 기초학력을 예측하는 예측모형을 개발하고, 다음 학년 예측에도 78%, 82%, 83% 의 정확도를 보이는 것을 확인하였다. 또한, 중학교 과목별 성취예측 의사결정트리를 그려서 과정을 분석해보면서, 성취 예측에 영향을 미치는 특성들은 어떠한 것들이 있는지 살펴보았다.